Therapeutic efficacy of FASN inhibition in preclinical models of HCC - Wang, Haichuan; Zhou, Yi; Xu, Hongwei; Wang, Xue; Zhang, Yi; Shang, Runze; O'Farrell, Marie; Rössler, Stephanie; Sticht, Carsten; Stahl, Andreas; Evert, Matthias; Calvisi, Diego F.; et al. (Hepatology, 2022)
Background and Aims: Aberrant activation of fatty acid synthase (FASN) is a major metabolic event during the development of HCC. We evaluated the therapeutic efficacy of TVB3664, a FASN inhibitor, either alone or in combination, for HCC treatment. Approach and Results: The therapeutic efficacy and the molecular pathways targeted by TVB3664, either alone or with tyrosine kinase inhibitors or the checkpoint inhibitor anti-programmed death ligand 1 antibody, were assessed in human HCC cell lines and multiple oncogene‐driven HCC mouse models. RNA sequencing was performed to elucidate the effects of TVB3664 on global gene expression and tumor metabolism. TVB3664 significantly ameliorated the fatty liver phenotype in the aged mice and AKT‐induced hepatic steatosis. TVB3664 monotherapy showed moderate efficacy in NASH‐related murine HCCs, induced by loss of phosphatase and tensin homolog and MET proto‐oncogene, receptor tyrosine kinase (c‐MET) overexpression. TVB3664, in combination with cabozantinib, triggered tumor regression in this murine model but did not improve the responsiveness to immunotherapy. Global gene expression revealed that TVB3664 predominantly modulated metabolic processes, whereas TVB3664 synergized with cabozantinib to down‐regulate multiple cancer‐related pathways, especially the AKT/mammalian target of rapamycin pathway and cell proliferation genes. TVB3664 also improved the therapeutic efficacy of sorafenib and cabozantinib in the FASN‐dependent c‐MYC‐driven HCC model. However, TVB3664 had no efficacy nor synergistic effects in FASN‐independent murine HCC models. Conclusions: This preclinical study suggests the limited efficacy of targeting FASN as monotherapy for HCC treatment. However, FASN inhibitors could be combined with other drugs for improved effectiveness. These combination therapies could be developed based on the driver oncogenes, supporting precision medicine approaches for HCC treatment.
Gesehen am 05.09.2023